2014
DOI: 10.1007/s10522-014-9508-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension in Caenorhabiditis elegans by several traditional Chinese medicine formulas

Abstract: There is considerable interest in using traditional Chinese medicine formulas (TCMF) to delay aging or treat age-related diseases. Due to cost and duration, the beneficial effects of TCMF on prolongation are mainly extrapolated from vitro studies or physiological indexes. Little is known about whether TCMF are beneficial in whole level, particularly with respect to lifespan. To address this issue, we selected eight formulas with anti-oxidative activity and examined their effects on the lifespan of Caenorhabdit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…These results gave evidences on that SM accelerated anti-oxidant responses of worms on a certain degree. Previous work in our lab has demonstrated that SM can extend C. elegans lifespan3. It is reasonable to believe that SM can specifically kill cancer cells, but not normal cells.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…These results gave evidences on that SM accelerated anti-oxidant responses of worms on a certain degree. Previous work in our lab has demonstrated that SM can extend C. elegans lifespan3. It is reasonable to believe that SM can specifically kill cancer cells, but not normal cells.…”
Section: Discussionmentioning
confidence: 87%
“…SM formula is composed of RG, RO, and FS (3:3:2) according to Chinese Pharmacopoeia (2015)3. RG (9 g), RO (9 g), and FS (6 g) were soaked in 130 mL ddH 2 O for 30 min, and then heated to boil and simmered gently with stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few studies have referred to its pharmacological effect on lifespan extension. Wan evaluated the lifespan extension effect of several TCM formulas, including LWDH, in C. elegans and found that this medicine could extend the lifespan, however, its mechanism remains unclear [7].…”
mentioning
confidence: 99%